2008
DOI: 10.1007/s00595-007-3678-2
|View full text |Cite
|
Sign up to set email alerts
|

Portomesenteric venous gas in acute bowel ischemia: Report of a case

Abstract: Portomesenteric venous gas and pneumatosis intestinalis (PI) are rare but important radiographic findings. They are usually discussed separately in the literature and little is known about the clinical importance of their combination in acute bowel ischemia. Abdominal computed tomography (CT) has proven useful for detecting subtle portomesenteric venous gas or PI in the early stages of acute bowel ischemia. Although the CT findings of either portomesenteric venous gas or PI as separate entities are not pathogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Mucosal integrity, intraluminal pressure, bacterial flora, and bowel gas all interact in the formation of intramural gas (4). Although image findings of either pneumatosis intestinalis or portomesenteric vein gas are not pathognomonic, evidence has shown that the combination of these rare findings indicates severe bowel wall damage, and this is strongly associated with fulminant bowel infarction, especially band-like pneumatosis (5,6). A simple abdominal plain film may provide a diagnosis, but CT is considered the best imaging modality, especially in the early stage.…”
Section: Discussionmentioning
confidence: 97%
“…Mucosal integrity, intraluminal pressure, bacterial flora, and bowel gas all interact in the formation of intramural gas (4). Although image findings of either pneumatosis intestinalis or portomesenteric vein gas are not pathognomonic, evidence has shown that the combination of these rare findings indicates severe bowel wall damage, and this is strongly associated with fulminant bowel infarction, especially band-like pneumatosis (5,6). A simple abdominal plain film may provide a diagnosis, but CT is considered the best imaging modality, especially in the early stage.…”
Section: Discussionmentioning
confidence: 97%
“…Complications occur in approximately 3% of PI cases and include obstruction, intussusception, volvulus, hemorrhage, bowel ischemia, and intestinal perforation. 2,3,11 Although various theories have been advanced in an attempt to explain the mechanism of PI formation, none have been incontrovertibly proven. The mechanism theory, which is the most widely accepted explanation, postulates that gas is forced into the bowel wall via breaks in the mucosa.…”
Section: Discussionmentioning
confidence: 97%
“…2,3 Clinical conditions associated with secondary PI can be classifi ed into the following 4 types: (1) life-threatening bowel necrosis, such as necrotizing enterocolitis, bowel ischemia and infarction, and neutropenic colitis; (2) mucosal disruption caused by peptic ulcer disease, bowel obstruction, abdominal trauma, previous endoscopy or surgery, and infl ammatory bowel disease; (3) increased mucosal permeability associated with steroid therapy, chemotherapy, connective tissue diseases, acquired immune defi ciency syndrome (AIDS), and immunosuppression following organ transplantation; and (4) pulmonary conditions, such as chronic obstructive pulmonary disease and asthma. 1,11 Pneumatosis intestinalis is an unusual condition that may be benign, but can indicate ischemic bowel and the need for surgical intervention. Greenstein et al recently reported that the overall in-hospital mortality rate was 20%, and the surgical rate was 35%.…”
Section: Discussionmentioning
confidence: 99%
“…It has numerous causes, predominantly mesenteric infarction, which is associated with poor prognosis [3,5]. Abdominal computed tomography (CT) has become the key imaging procedure used to diagnose acute bowel ischemia and to detect faint signs of portomesenteric venous gas [6][7][8][9]. The radiologic presentation has some particularities that physicians must be aware of to avoid delaying treatment.…”
Section: Portomesenteric Venous Gas In Acute Small Bowel Infarction Amentioning
confidence: 99%